Contribuições de Joaquim Felicio dos Santos para o direito das sucessões no Brasil: fragmentos da história do código civil brasileiro - Felipe Quintella Machado de Carvalho (2017)
Within the scope of the history of the sources of the Law, specifically, the history of the Civil Code, this thesis examines the history of the Law of Succession rules in the Civil Code of 1916 to establish whether or not such Code received contributions from Joaquim Felicio dos Santos’s Civil Code Project. It starts from a study of the Law of Succession rules in the Law prior to the Civil Code. Moreover, it goes through important biographical issues of Felicio dos Santos, as well as the main facts in the history of his Civil Code Project. Then, a study of the Law of Succession rules in such Project is carried out. Furthermore, the main facts in the history of Clovis Bevilaqua’s Civil Code Project is presented, from 1899 to when it became the Civil Code in 1916. Lastly, the thesis analyses the documents regarding the Law of Sucession rules in the discussions of the Civil Code, and reveals the contributions that such Code received from Felicio dos Santos’s Project.